2019
DOI: 10.1007/s10508-019-01549-1
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Turner Syndrome: A Systematic Review

Abstract: Turner syndrome (TS) is a genetic condition characterized by partial or complete monosomy X. Alterations in hormonal function, height, and peer relationships, among other features and correlates of TS, appear to be risks for depressive illness. In order to summarize what is known about depression in Turner syndrome, with the aim of determining if individuals with TS are at increased risk for depression, a literature search and analysis was conducted. In total, 69 studies were identified and 35 met criteria of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…Differences in development of the dorsolateral prefrontal cortex, orbitofrontal cortex, amygdala, and hippocampus have been described as drivers of this neurocognitive phenotype [2][3][4][5]. This phenotype includes difficulties with visual-spatial skills, nonverbal problem solving, social cognition (i.e., perceiving and processing social cues), and executive functioning [2,[6][7][8][9][10]. Additionally, prior studies have demonstrated an increased prevalence of mood disorders, including depression and anxiety, in TS individuals with a lifetime prevalence around 50% [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…Differences in development of the dorsolateral prefrontal cortex, orbitofrontal cortex, amygdala, and hippocampus have been described as drivers of this neurocognitive phenotype [2][3][4][5]. This phenotype includes difficulties with visual-spatial skills, nonverbal problem solving, social cognition (i.e., perceiving and processing social cues), and executive functioning [2,[6][7][8][9][10]. Additionally, prior studies have demonstrated an increased prevalence of mood disorders, including depression and anxiety, in TS individuals with a lifetime prevalence around 50% [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…Unpartnered women with TS report very low-level sexual functioning and delayed sexual activity, but in partnered women with TS, sexual function appears similar to that in women without the condition (Cardona Attard et al, 2020;Pavlidis et al, 1995;Sheaffer et al, 2008). Consistent with the quality of life findings, TS is associated with higher rates of mood and anxiety disorders which tend to onset after adolescence (Anam et al, 2007;Cardoso et al, 2004;de Vries et al, 2019;Hutaff-Lee et al, 2019;Kilic et al, 2005;Liedmeier et al, 2020;Moonga et al, 2017;Morris et al, 2020), and related traits such as irritability ; severe postpartum depression with psychotic features has been described in one patient with TS who gave birth following egg donation (Shea and Wolfman, 2017). There is some evidence that individuals with Turner syndrome, particularly mosaic subjects, are at increased risk of schizophrenia, a psychotic disorder with neurodevelopmental antecedents (Jung et al, 2014;Lee et al, 2018;Mavrogiorgou et al, 2019;Prior et al, 2000;Roser and Kawohl, 2010).…”
Section: Turner Syndromementioning
confidence: 90%
“…Each of the sections solicited the pediatric endocrinology provider's perspective on the following outcomes: (1) are patients with TS being screened and if so, what does this look like? (2) what are the barriers to screening? (3) could a short, validated screening tool be implemented in the pediatric endocrine clinic setting?…”
Section: Survey Developmentmentioning
confidence: 99%
“…Girls with TS are at a greater risk for neurodevelopmental (ND) delays and/or MH diagnoses than the general population, with potential adverse effects observed in all health domains. Up to 75% of girls with TS have a learning disability, ∼25% have attentiondeficit hyperactivity disorder, and over half will experience symptoms of anxiety and/or depression [1,2]. Despite how prevalent these conditions are and their known effect on academic achievement and quality of life, symptom recognition is often delayed or missed altogether in girls with TS.…”
Section: Introductionmentioning
confidence: 99%